2017
DOI: 10.13175/swjpcc034-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of spousal involvement in continuous positive airway pressure (CPAP) adherence in patients with obstructive sleep apnea (OSA)

Abstract: Introduction Little is known about the impact of spousal involvement on continuous positive airway pressure (CPAP) adherence. The aim of this study was to determine whether spouse involvement affects adherence with CPAP therapy, and how this association varies with gender. Methods 194 subjects recruited from Apnea Positive Pressure Long Term Efficacy Study (APPLES) completed the Dyadic Adjustment Scale (DAS). The majority of participants were Caucasian (83%), and males (73%), with mean age of 56 years, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Interestingly, the older retired couple cluster presented a lower ESS score and an alteration in quality of life related to OSA at baseline compared to the two other couple clusters. Nevertheless, our data are consistent with previous findings showing that increased age is associated with higher adherence to CPAP [ 24 , 25 ] even though other authors have found inconsistent findings [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the older retired couple cluster presented a lower ESS score and an alteration in quality of life related to OSA at baseline compared to the two other couple clusters. Nevertheless, our data are consistent with previous findings showing that increased age is associated with higher adherence to CPAP [ 24 , 25 ] even though other authors have found inconsistent findings [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study examining the role of spousal involvement in CPAP adherence found that spousal involvement is important in determining CPAP compliance in men in the six months after CPAP initiation but does not predict long-term adherence [ 25 ]. The authors of this study suggest that involvement of the spouse should be considered an integral part of CPAP initiation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of others' involvement with the patient's condition and the particular importance of partner support have been reported by Elfström et al 40 and Luyster et al 29 Our findings suggest that the positive role of partner support extends to the positive effect of the peer coaching session in the group visit, both of which demonstrate the potential value of a socially supportive environment in motivating adherence to PAP treatment. 41,42 Attitude: Wanting to Live and Determination Another human and highly emotional factor that serves to motivate adherence to treatment is the role of close family ties, particularly grandchildren and spouses, and the desire to live that is fostered by these relationships-partner to spouse: "I want you to be an old dude with me."…”
Section: Support: Partner and Peersupporting
confidence: 74%
“…28 Another survey of married patients with OSA demonstrated that level of spousal involvement was associated with increased continuous positive airway pressure (CPAP) adherence at 6 months. 29 Bouloukaki et al in their intensive versus standard follow-up study had required the patient to bring partner or family to follow-up care; however, which component of the intensive treatment produced the major effect in improving PAP adherence was not assessed. 16 The findings of the first qualitative analysis of both patient and partner experiences 30 with OSA and the results of the first randomized controlled trial of couples intervention supports engagement of partners in improving PAP adherence.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Importantly, acceptance has been reported as a predictor of long-term CPAP adherence. 21 Adherence, in particular, may be influenced by a myriad of factors, 22 including OSA severity, preexisting hypertension, 23 level of functioning (ie, daytime and nocturnal) at time of diagnosis, 24 spousal involvement in treatment, 25 problems with device use (eg, mask fit), psychological disposition, nasal stuffiness, claustrophobia, reticence toward treatment, disturbance of bed partner, 26 and financial cost. 27 With regard to the latter, patients with low socioeconomic status or those experiencing financial crisis have lower rates of adherence and reduced access to treatment.…”
Section: Introductionmentioning
confidence: 99%